Hate crime in Canada: A quantitative analysis of victimization survey data. - Edgar, Jill Marie. (University of Ottawa (Canada), 2002)
Hate crime victimization in Canada is a criminal justice issue that has received insufficient attention. To address this lack of information, Statistics Canada included two questions concerning hate crime on the 1999 administration of the General Social Survey. The data from this survey were analyzed for this thesis. Differences between hate crime and non-hate crime respondents were examined. Subsequently, the three most frequently reported hate crime motivation categories of race/ethnicity, sex and culture were compared. The results of the analysis revealed that while differences exist between hate crime and non-hate crime respondents, the main differences appeared between respondents reporting sex-motivated hate crimes and those in the two remaining categories of race/ethnicity and culture. The main variations were in the reasons respondents cited for not reporting the incident to the police and their psychological reactions to the event. Those who perceived their victimization to be based upon their race/ethnicity or culture did not report the incident to the police because they felt it was not important enough. Respondents victimized on the basis of their sex indicated that they did not bring the incident to the attention of the police because they felt the "police do nothing". While respondents of the three motivation categories of hate crime examined in this study reported being fearful as a result of their victimization, respondents who perceived themselves as having been the victim of a sex-based hate crime were substantially less likely than those victimized as a result of their race/ethnicity or culture to report that they were not effected that much.
Keywords: Canadian Studies.